Deep Procedural Analysis of the Judicial Manager’s Role in Simplified Insolvency Proceedings: Legal Doctrines and Judicial Practice - Toksanbaeva, Ayjamal (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
• This research paper delves into the complex procedural mechanics of simplified insolvency within the economic judicial system of Uzbekistan. It identifies the “procedural compression” phenomenon, where the Judicial Manager is required to bypass the traditional observation and rehabilitation phases to achieve rapid liquidation. The article provides a doctrinal analysis of the Judicial Manager's status as a “procedural trustee”, examining the legal tension between administrative efficiency and the constitutional protection of property rights. By analyzing the “Missing Debtor” and “Asset-less Estate” doctrines, the author proposes a new conceptual framework for the Judicial Manager’s liability and remuneration. The study advocates for the integration of summary judgment principles into insolvency litigation to prevent the abuse of simplified tracks by unscrupulous debtors.